Lymphorrhea: An unusual complication of jugular venous catheterization for hemodialysis - D Bajpai (Indian Journal of Nephrology, 2018)
A considerable number of end-stage renal disease patients undergo tunneled cuffed catheter insertion for hemodialysis under ultrasonographic guidance while awaiting arteriovenous fistula creation. We report a case of a 62-year-old female who underwent tunneled catheter insertion in the left internal jugular vein under ultrasound and fluoroscopic guidance, which was followed by pericatheter serous discharge. Fluid examination confirmed the diagnosis of lymphorrhea, and lymphoscintigraphy facilitated its localization. This case is reported for its rarity and with a discussion on literature review, complications of lymphorrhea, and their management.